1999
DOI: 10.1295/polymj.31.150
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Aeromonas Gum in Aqueous Solution

Abstract: Aero monas (A) gum, a stabilizer, and thickening agent of food, is composed of xylose, mannose, galactose, glucose, and mannuronic acid. Weight-average molecular weights M wand intrinsic viscosities [ry] of the unfractionated A gum and three fractions in water, 0.5 M NaCI aqueous solution and cadoxen were studied by light scattering and viscometry, Experimental results showed that A gum exists as an aggregate in 0.5 M NaCl aqueous solution and mainly as a single chain in cadoxen, The apparent aggregation numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The previous A gum fraction (A-5), 14 which was fractionated by reprecipitation from pure water as a solvent to isopropanol as a precipitant, was used for the present work. The weight-average molecular weight (M w ) and intrinsic viscosity ( …”
Section: Experimental Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The previous A gum fraction (A-5), 14 which was fractionated by reprecipitation from pure water as a solvent to isopropanol as a precipitant, was used for the present work. The weight-average molecular weight (M w ) and intrinsic viscosity ( …”
Section: Experimental Samplementioning
confidence: 99%
“…13 Recently, we have confirmed that the A gum forms aggregates in a salt aqueous solution 14 -16 and the aggregates are broken into single chains in cadoxen 14 and dimethylsulfoxide (DMSO) containing 0.20M lithium chloride (LiCl). [17][18] However, cadoxen is prepared with cadmium oxidation and it is poisonous.…”
Section: Introductionmentioning
confidence: 96%
“…[13][14][15] Aeromonas gum, a stabilizer and thickening agent of food, exists as an aggregate in 0.5 M NaCl aqueous solution and as a single chain in cadoxen. 7 These results indicated that polysaccharides have generally a tendency to aggregate in aqueous solution because of the abundance of inter-chain hydrogen bonds. In this work, components, apparent weight-average molecular weight M w , mean molecular size, aggregation behavior of E gum in aqueous solution were determined by the IR, high-performance liquid chromatography (HPLC), static and dynamic light scattering, and GPC.…”
Section: Introductionmentioning
confidence: 98%
“…and the aggregation resulted from inter-chain interaction. 6,7 Recently, much attention has been paid to the polymer aggregation, which play an important role in the thickening, micellization, gelation and microencapsulation etc.. The aggregation process in dilute solution, 8 aggregation mechanism, 9 aggregation behavior, 10 and the effects of temperature and polymer concentration on the aggregation of polymers 5,11,12 have been studied by static and dynamic light scattering, combining gel permeation chromatography (GPC) with infrared (IR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…A gum is composed of xylose, mannose, galactose, glucose, and mannuronic acid, and E gum contains fucose, galatose, glucose and glucuronic acid. 3,4 The various extracellular polysaccharides produced from Aeromonas solmvnicida and Erwinia chrysanthemi have been reported 5,6 ; however, studies relating to miscibility are rarely published. It is well known that xanthan and pectin are normally used as additives for foods and cosmetics.…”
Section: Introductionmentioning
confidence: 99%